Article Desktop Based National Police Commission Activities Information System - Asep Hendri Hendri; Mochammad Arief Sutisna (Universitas Muhammadiyah Riau, 2021)
In the implementation of the activities of the National Police Commission (Kompolnas) every month it is necessary to prepare a monthly report by the Secretariat of the National Police Commission to be reported to the Chair of the National Police, so that it can be used as a benchmark for the implementation of Kompolnas performance. However, making monthly reports is often late and mistaken because there are factors that influence, including: data storage such as official travel administration and irregular activity schedules making it difficult to find data, difficult to monitor ongoing activities, many activities implemented and others. In this regard, a desktop-based information system for the implementation of Kompolnas is required. The research method uses Research and Development to create a desktop-based Kompolnas activity information system. Meanwhile, the data teaching technique used literature study and field study (interview and document examination). Then the system development method used is the waterfall method which has several stages, namely: needs analysis, system design, coding & testing, program implementation, and maintenance. The research resulted in a supporting information system for compiling a monthly report on Kompolnas activities because data on Kompolnas activities such as reference documents, orders, materials, photos / videos, are easy to input and can be viewed, downloaded and printed. In doing so, it can realize a paperless office, thus giving the printer paper, ink and time.